Genetic polymorphisms as predictors of methotrexate toxicity: literature review - G. A. Radzhabova; T. T. Valiev; Yu. E. Ryabukhina; M. I. Savelyeva; Sh. P. Abdullaev; O. D. Gurieva; P. A. Zeynalova (Онкогематология, 2024)
Background. A significant advancement in the treatment of high-grade aggressive non-Hodgkin’s lymphomas and acute lymphoblastic leukemia is the inclusion of high-dose (1000–5000 mg/m2) methotrexate in the treatment protocol. This approach has significantly increased the long-term survival rate, but it has been associated with toxicity, requiring supportive care. Factors that predict toxicity were identified, including genes involved in the metabolism (MTHFR) or transport (SLCO1B1) of methotrexate. The analysis of methotrexate metabolism has identified additional genes responsible for the elimination of this drug, allowing for more effective prevention and treatment of methotrexate-associated toxicity.Aim. To study the genetic polymorphisms of enzymes involved in the methotrexate metabolism and associated toxicity in the treatment of pediatric acute lymphoblastic leukemia and non-Hodgkin’s lymphomas.Materials and methods. Data were analyzed in specialized medical databases such as Pubmed, Scopus, Web of Science, Frontiers, and Google Scholar from 2001 to 2024.Results. The main predictors of high-dose methotrexate-associated toxicity are gene polymorphisms in MTHFR, SLCO1B1, ARID5B.Conclusion. Despite the contradictory data presented in the literature, it is important to consider the detection of polymorphisms during high-dose methotrexate treatment in order to administer timely supportive care and prevent significant toxicity.